Examining virulence plasmid loss in Yersinia pseudotuberculosis - Dunlop, Jake (2021)
The genus Yersinia is composed of eleven species, three of which (Y. pseudotuberculosis, Y. enterolitica, and Y. pestis) are human pathogens. It is believed that Y. pseudotuberculosis is the predecessor of Y. pestis, which causes plague, and as a result there is a close genetic link between the two species. Each of the pathogenic species possess an approx. 70 kb plasmid known as pYV, (pCD1 in Y. pestis and pYVe in Y. enterocolitica) which is essential for virulence. The plasmid codes for a Type III Secretion system (T3SS) composed of structural proteins which form an injectisome (analogous to a hypodermic needle) and effectors which when combined disarm host immune cells through disruption of processes such as actin polymerisation as well as inducing cellular apoptosis. Expression of these proteins, usually referred to as Yops, are known to be regulated by both the environment (through temperature and calcium concentration) and the bacterial cell-to-cell signalling system known as Quorum Sensing (QS).